Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top


$$yU_{xy} + 2U_x = x \\ U=U(x,y) $$

I have the solution to this question. I was told to integrate over $x$ at first. After integrating over $x$ I obtained: $$yU_y + 2yU= (x^2)/2 +yC(y)$$ Then to solve further, one can use an integrating factor $m(y)=y$. My question is how to find this integrating factor?

share|cite|improve this question
I don't think you integrated over $x$ correctly. It should be $$ yU_y + 2U = \frac {x^2}2 + f(y) $$ – Kaster Feb 15 '13 at 20:09

Anyway, that's how I'd solve it: $$ yU_{xy} + 2U_x = x \\ yU_y + 2U = \frac {x^2}2 + f(y) \\ U_y + \frac 2y U = \frac {x^2}{2y} + \frac {f(y)}y $$ General rule to find integrating factor is $$ M(y) = e^{\int P(y)dy} $$ if you equation looks like $$ U_y + P(y)U = Q(x,y) $$ In your case $P = \frac 2y$, so $M(y) = e^{\int \frac 2y dy} = e^{2\ln y} = y^2$. So multiply your equation to $M(y)$ to get full differential on the left $$ y^2U_y+2yU = (y^2U)_y = \frac {x^2y}2+yf(y) $$ After the integration over $y$ $$ y^2U = \frac {x^2y^2}4+F(y)+G(x) \\ U = \frac {x^2}4 + \frac{F(y)}y + \frac {G(x)}{y^2} $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.